Hiperplasia Congénita da Suprarrenal de Expressão Tardia por Deficiência de 21-Hidroxilase - Vieira, A (2011)
The deficiency of the enzyme 21-hydroxylase (21-HO) is responsible for about 90% to 95% of all cases of congenital adrenal hyperplasia (HCSR). This disorder is one of the most frequent hereditary illnesses of autosomal recessive trait. The illness can be presented in two clinical forms: 1 - classic, subdivided in saltwasting form and simple virilizing form; 2 - nonclassic or late-onset. The severity of the illness is correlated with the degree of enzymatic activity of 21-HO, which depends on the type of mutation that occurs in gene CYP21A2. The late onset congenital adrenal hyperplasia is that one where the enzymatic blockade is less intense. The clinical is variable: precocious pubarche, polycystic ovaries, hirsutism, oligoamenorrhea, acne and infertility. Gold standard for the diagnosis of late onset congenital adrenal hyperplasia consists on the test of the tetracosactide, considering itself diagnostic positive when 17-hidroxiprogesterona (17-OHP) is higher of 10-15 ng per mL. Many patients don't need treatment; however, if necessary, such a treatment essentially consists on the Administration of glucocorticoids and antiandrogens. Considering that affected individuals and the carriers may have a severe mutation in CYP21A2, they can have descendents with the classic form (if their partner is also a carrier of a severe mutation), it is mandatory the genetic study of the couple. The authors illustrate the importance of this genetic study through five clinical cases, whose common link is the desire to have children, as well as the presence on the feminine element of late onset congenital adrenal hyperplasia. The genetic study of the couple allows adequate pre-conception counseling and also prevents the use of corticoids throughout the pregnancy (if there's no risk of descendents being affected with the classic form). This aspect must be had in account in programming the pregnancy, in order to prevent therapeutics and unnecessary distrusts.